High-airtightness geopolymer condensate as well as preparation method and application thereof

By using water glass and sodium hydroxide exciter in the preparation of the local polymer cured product, and adjusting the water-glue ratio and nanopowder additive ratio, the problem of mechanical performance of the local polymer is reduced when improving the liquid-solid ratio is achieved, High airtightness and good mechanical strength.

CN119430749AActive Publication Date: 2025-02-14CHINA NAT PETROLEUM CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411335355.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-14
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

When the existing polymers increase the liquid-solid ratio to increase the flowability, they will cause the initial water content to significantly reduce its mechanical properties and extend the curing time, affecting density and stability.

Method used

When preparing the ground polymer cured product, an exciter consisting of water glass and sodium hydroxide is used, and stirred and mixed according to a specific water-glue ratio and nanopowder additive ratio, a high airtight polymer curing is prepared. Things.

Benefits of technology

Without increasing the liquid-solid ratio, the compactness and mechanical strength of the ground polymer are significantly improved, the curing time is shortened, the airtight performance is improved, and its application scenarios and fields are broadened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430749A_ABST
    Figure CN119430749A_ABST
Patent Text Reader

Abstract

The invention discloses a high-airtightness geopolymer condensate as well as a preparation method and application thereof, and the method comprises the following steps: adding an exciting agent consisting of water glass and sodium hydroxide into water, heating and uniformly stirring to obtain a micelle solution, and cooling to room temperature for later use; weighing the fly ash and the nano-powder additive according to a water-binder ratio of the total amount of water and added water in the water glass to the total amount of the fly ash and the additive of 0.3, and pouring the fly ash and the nano-powder additive into a stirring pot of a cement mortar stirrer for preliminary mixing; and pouring the micellar solution into a stirring pot, and stirring and mixing the micellar solution with the preliminarily mixed fly ash and nano-powder additive to prepare the geopolymer condensate. According to the method, the defects that the initial water content in the existing geopolymer is increased due to a large liquid-solid ratio, the mechanical property of the geopolymer is remarkably reduced, and the curing time is prolonged are overcome, the compactness of the geopolymer is remarkably improved compared with that of the existing geopolymer, and the method has very important practical significance for widening the application scene and the application field of the geopolymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of geopolymer-based materials, and in particular to a high-air-tightness geopolymer solidified material, a preparation method and applications thereof. Background Art

[0002] Geopolymer is a type of gel material with a three-dimensional network inorganic polymer structure formed by silicon oxide tetrahedron and aluminum oxide tetrahedron. It was first developed by French Professor Davidovits in the late 1970s. The structure is between quasi-crystalline and amorphous. It does not have a specific chemical formula and is usually represented by the general chemical formula M x [-(Si-O2) z -Al-O] n ·ωH2O, where M is an alkali metal cation, z is the molar ratio of Si / Al in the structure, n represents the degree of polymerization, and ω represents the number of chemically bound water. Due to this unique network-like polymer structure, these materials possess stable physical and chemical properties, including high strength, high temperature resistance, and resistance to acid and alkali corrosion. They have broad applications in fire protection and thermal insulation, construction, heavy metal solidification, and nuclear waste consolidation. Summary of the Invention

[0003] In order to improve the density of geopolymers without increasing the liquid-to-solid ratio and to enable the geopolymers to have good mechanical strength and stability, thereby enriching technical routes and increasing the selection space, the embodiments of the present invention provide a high-airtightness geopolymer solid, a preparation method and its application.

[0004] In a first aspect, an embodiment of the present invention provides a method for preparing a highly airtight geopolymer solidified material, which may include:

[0005] Add an activator consisting of water glass and sodium hydroxide into water, heat and stir to obtain a micellar solution, and then cool to room temperature for use;

[0006] Weigh the fly ash and the nano-powder additive so that the total amount of water in the water glass and the added water is equal to the total amount of fly ash and the nano-powder additive in a water-to-binder ratio of 0.3, and pour the fly ash and the nano-powder additive into a mixing pot of a cement mortar mixer for preliminary mixing; wherein the alkali content of the activator accounts for 9% to 16% of the total amount of the fly ash and the nano-powder additive; and the nano-powder additive accounts for 1% to 20% of the total amount of the fly ash and the nano-powder additive;

[0007] The micelle solution is poured into the stirring pot, and stirred and mixed with the preliminarily mixed fly ash and the nano-powder additive to prepare the geopolymer solidified material.

[0008] In one embodiment, the alkali content in the activator accounts for 10% to 16% of the total ash content of the fly ash and the nano-powder additive; the nano-powder additive accounts for 1% to 3% of the total ash content of the fly ash and the nano-powder additive, or the nano-powder additive accounts for 10% to 20% of the total ash content of the fly ash and the nano-powder additive.

[0009] In another embodiment, the alkali content in the activator accounts for 13% to 16% of the total ash content of the fly ash and the nanopowder additive; and the nanopowder additive accounts for 10% to 20% of the total ash content of the fly ash and the nanopowder additive.

[0010] In another embodiment, the modulus of the water glass is 0.5-2.5.

[0011] In another embodiment, the nanopowder additive is at least one of the following nanopowders: nanooxide, nanononmetal, and nanometal.

[0012] In another embodiment, in the above steps, the micellar solution is obtained by heating and stirring uniformly, wherein the heating parameter is heating to 60° C., and the stirring parameter is stirring for 30 minutes.

[0013] In another embodiment, the stirring parameters for mixing the micelle solution with the coal powder and the nanopowder additive in the above step are: first stirring slowly for 2 minutes, then stirring rapidly for 2 minutes.

[0014] In a second aspect, an embodiment of the present invention provides a highly airtight geopolymer solidified material prepared according to the method for preparing a highly airtight geopolymer solidified material according to the first aspect.

[0015] In a third aspect, an embodiment of the present invention provides an application of a high-airtightness geopolymer solidified material prepared by the method for preparing a high-airtightness geopolymer solidified material according to the first aspect in a construction project.

[0016] In a fourth aspect, an embodiment of the present invention provides a use of a high-gas-tightness geopolymer solidified material prepared by the method for preparing a high-gas-tightness geopolymer solidified material as described in the first aspect in well completion or cementing.

[0017] The beneficial effects of the above technical solutions provided by the embodiments of the present invention include at least:

[0018] Embodiments of the present invention provide a highly airtight geopolymer solidified material, a preparation method, and its application. This preparation method improves the compactness of the geopolymer without increasing the liquid-to-solid ratio, while also imparting excellent mechanical strength and stability to the geopolymer. This method overcomes the drawback of existing geopolymers, which suffer from high liquid-to-solid ratios, significantly reducing their mechanical properties and prolonging their curing time. Furthermore, compared to existing geopolymers, the compactness of the geopolymer is significantly improved, significantly broadening the application scenarios and fields of geopolymers.

[0019] Other features and advantages of the present invention will be described in the following description, and in part will become apparent from the description, or will be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures particularly pointed out in the written description and the accompanying drawings.

[0020] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0022] Figure 1 The present invention provides a flow chart of a method for preparing a highly airtight geopolymer solidified material according to an embodiment of the present invention. DETAILED DESCRIPTION

[0023] Exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. Rather, these embodiments are provided to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.

[0024] The inventors found in actual applications that due to the high viscosity of the water glass solution, the fluidity of the geopolymer is poor, and it is necessary to increase the fluidity by increasing the liquid-solid ratio to meet the construction requirements; however, actual research shows that an excessively large liquid-solid ratio will also bring some negative effects. For example, the fly ash particle size has a significant impact on the water demand behavior of the cementitious material. With the increase of the amount of large-particle fly ash, the water demand tends to increase; increasing the initial water content in the geopolymer will significantly reduce the 7-day curing performance and increase the total volume of the geopolymer pores; a large liquid-solid ratio can accelerate the dissolution of the raw materials. 4+ 、Al 3+Hydrolysis of the compound can also hinder the polycondensation reaction, thereby prolonging the curing time. Prolonged curing reduces the non-volatile water content, leading to a decrease in compressive strength. Therefore, it is necessary to develop a geopolymer and its preparation method that can improve the density of the geopolymer without increasing the liquid-to-solid ratio, while also providing good mechanical strength and stability. This is of great practical significance for expanding the application of geopolymers.

[0025] The present invention provides a method for preparing the above-mentioned high airtightness geopolymer solidified material, referring to Figure 1 As shown, the preparation method may include the following steps:

[0026] Step S11: Add an activator consisting of water glass and sodium hydroxide to water, heat and stir to obtain a micellar solution, and then cool to room temperature for later use. The modulus of the water glass is 0.5 to 2.5. In this step, heat and stir to obtain a micellar solution. The heating parameters are heating to 60° C. and stirring parameters are stirring for 30 minutes.

[0027] Step S12: Weigh fly ash and nanopowder additives so that the total amount of water in the water glass and the added water is equal to the total amount of fly ash and nanopowder additives, and pour the fly ash and nanopowder additives into the mixing pot of a cement mortar mixer for preliminary mixing; wherein the alkali content of the activator is 9% to 16% of the total amount of fly ash and nanopowder additives; and the nanopowder additives are 1% to 20% of the total amount of fly ash and nanopowder additives. The nanopowder additive is at least one of the following nanopowders: nano-oxides, nano-nonmetals, and nano-metals.

[0028] Step S13: Pour the micelle solution into a stirring pot and stir and mix it with the preliminarily mixed fly ash and nanopowder additive to prepare a geopolymer solidified material. In this step, the mixing parameters for the micelle solution, the pulverized coal, and the nanopowder additive are: first, slowly stirring for 2 minutes, then rapidly stirring for 2 minutes.

[0029] The method for preparing a highly airtight geopolymer solidified material provided in the embodiments of the present invention improves the compactness of the geopolymer without increasing the liquid-to-solid ratio, while also imparting excellent mechanical strength and stability. This method overcomes the drawback of existing geopolymers, which suffer from high liquid-to-solid ratios, significantly reducing their mechanical properties and prolonging their curing time. Furthermore, it significantly improves the compactness of the geopolymer compared to existing geopolymers, possessing significant practical significance for broadening the application scenarios and fields of geopolymers.

[0030] In a preferred embodiment, the alkali content of the activator accounts for 10% to 16% of the total ash content of the fly ash and the nanopowder additive; the nanopowder additive accounts for 1% to 3% of the total ash content of the fly ash and the nanopowder additive, or the nanopowder additive accounts for 10% to 20% of the total ash content of the fly ash and the nanopowder additive. In this embodiment of the present invention, by adjusting the various components of the geopolymer, the synergistic effect between the components is enhanced, significantly improving the airtightness of the high-airtightness geopolymer solid without affecting its mechanical strength and stability.

[0031] In another more preferred embodiment, the alkali content of the activator accounts for 13% to 16% of the total fly ash and nanopowder additive, and the nanopowder additive accounts for 10% to 20% of the total fly ash and nanopowder additive. The synergistic effect between the various geopolymer components in this embodiment of the present invention is further enhanced, resulting in more significant airtightness performance.

[0032] Based on the above preparation method, the following examples and comparative examples are provided in the present invention to verify the airtightness effect of the high airtightness geopolymer cured product prepared in the present invention.

[0033] The water glass modulus used in Examples 1 to 9 of the present invention and Comparative Examples 1 to 9 is 3.3, wherein the mass ratio of each component is 26.5% SiO2 content, 8.3% Na2O content, and 65.2% H2O content. The above water glass modulus in the examples of the present invention can be adjusted according to the content of NaOH added in the activator. This process requires adjusting the water glass modulus using an existing calculation formula to determine the content of NaOH added. The specific specifications of the nanopowder additives in the examples of the present invention are shown in the following table:

[0034] Reagent name Specification or purity Nano-titanium dioxide 99.8% metals basis, 60nm, anatase, hydrophilic Nanosilica 99% metals basis, 30nm Nano-cobalt ferrite <100nm, 99% Nano-barium titanate 99.9%metals basis,<100nm Nano boron nitride 99.8%metals basis,<150nm Nano silicon powder ≥99.9%metals basis,20-60nm Nano copper-nickel alloy powder ≥98%,≤100nm Nano iron powder 99.9% metals basis, 100-300nm Nanocarbon powder ≥99.5%metals basis,powder,30nm

[0035] It should also be noted that the other raw materials and reagents involved in the examples and comparative examples of the present invention are all commercially available general reagent products.

[0036] Example 1:

[0037] Weigh 219.06 g of water glass, add it to 157.17 g of water, heat it to 60°C, stir it evenly, cool it to room temperature, add 53.96 g of NaOH to the above solution, stir it for 30 minutes, and obtain a uniform micellar solution with a water glass modulus of 1.0. Leave it for 24 hours before use.

[0038] Weigh 900g of fly ash at a water-cement ratio of 0.3 and pour it into the mixing pot of a cement mortar mixer. Then weigh 100g of nano-titanium dioxide and pour it into the mixing pot of the cement mortar mixer. Use a cement scraper to preliminarily mix the two powders. Add the micellar solution and stir slowly for 2 minutes, then rapidly for 2 minutes. Then, place the mixture into a triple mold. Secure the triple mold to a vibrating table and compact the material. Cover with plastic wrap and place in a constant temperature and humidity curing chamber for curing at 90% humidity and 30°C. Curing times are 14 days, 28 days, 56 days, and 63 days. Samples are removed from each chamber and tested for their strong air permeability coefficient.

[0039] As a control group of Example 1, Comparative Example 1 completed the following test:

[0040] Weigh 219.06 g of water glass, add it to 157.17 g of water, heat it to 60°C, stir it evenly, cool it to room temperature, add 53.96 g of NaOH to the above solution, stir it for 30 minutes, and obtain a uniform micellar solution with a water glass modulus of 1.0. Leave it for 24 hours before use.

[0041] Weigh 1000g of fly ash at a water-binder ratio of 0.3 and pour it into the mixing pot of a cement mortar mixer. Add the micellar solution and stir slowly for 2 minutes, then rapidly for 2 minutes. Place the mixture into a triple mold. Secure the triple mold to a vibrating table and compact the material. Cover with plastic wrap and place in a constant temperature and humidity curing chamber for curing at 90% humidity and 30°C. Curing times are 14, 28, 56, and 63 days. Samples are then taken from each chamber and tested for their air permeability coefficient.

[0042] The experimental results of the air permeability coefficient of Example 1 and Comparative Example 1 are shown in Table 1 as follows:

[0043] Table 1 Test results of air permeability coefficient of Example 1 and Comparative Example 1

[0044]

[0045]

[0046] Example 2:

[0047] Weigh 350.49 g of water glass, add it to 71.48 g of water, heat it to 60°C, stir it evenly, cool it to room temperature, add 39.88 g of NaOH to the above solution, stir it for 30 minutes, and obtain a uniform micellar solution with a water glass modulus of 1.6. Leave it for 24 hours before use.

[0048] Weigh 800g of fly ash at a water-cement ratio of 0.3 and pour it into the mixing pot of a cement mortar mixer. Weigh 200g of nano-silica and pour it into the mixing pot of the cement mortar mixer. Use a cement scraper to preliminarily mix the two powders. Add the micellar solution and stir slowly for 2 minutes, then rapidly for 2 minutes. Then, place the mixture into a triple mold. Secure the triple mold to a vibrating table and compact the material. Cover with plastic wrap and place in a constant temperature and humidity curing chamber for curing at 90% humidity and 30°C. Curing times are 14 days, 28 days, 56 days, and 63 days. Samples are removed from each chamber and tested for their strong air permeability coefficient.

[0049] As a control group of Example 2, Comparative Example 2 completed the following test:

[0050] Weigh 350.49 g of water glass, add it to 71.48 g of water, heat it to 60°C, stir it evenly, cool it to room temperature, add 39.88 g of NaOH to the above solution, stir it for 30 minutes, and obtain a uniform micellar solution with a water glass modulus of 1.6. Leave it for 24 hours before use.

[0051] Weigh 1000g of fly ash at a water-binder ratio of 0.3 and pour it into the mixing pot of a cement mortar mixer. Add the micellar solution and stir slowly for 2 minutes, then rapidly for 2 minutes. Place the mixture into a triple mold. Secure the triple mold to a vibrating table and compact the material. Cover with plastic wrap and place in a constant temperature and humidity curing chamber for curing at 90% humidity and 30°C. Curing times are 14, 28, 56, and 63 days. Samples are then taken from each chamber and tested for their air permeability coefficient.

[0052] The experimental results of the air permeability coefficient of Example 2 and Comparative Example 2 are shown in Table 2 as follows:

[0053] Table 2 Test results of air permeability coefficient of Example 2 and Comparative Example 2

[0054]

[0055] Example 3:

[0056] Weigh 219.14 g of water glass, add it to 142.87 g of water, heat it to 60°C, stir it evenly, cool it to room temperature, add 15.26 g of NaOH to the above solution, stir it for 30 minutes, and obtain a uniform micellar solution with a water glass modulus of 2.0. Let it stand for 24 hours before use.

[0057] Weigh 950g of fly ash, using a water-cement ratio of 0.3, and pour it into the mixing pot of a cement mortar mixer. Then, weigh 50g of nano-cobalt ferrite and pour it into the mixing pot of the cement mortar mixer. Use a cement scraper to preliminarily mix the two powders. Add the micellar solution and stir slowly for 2 minutes, then rapidly for 2 minutes. Then, place the mixture into a triple mold. Secure the triple mold to a vibrating table and compact the material. Cover with plastic wrap and place in a constant temperature and humidity curing chamber for curing at 90% humidity and 30°C. Curing times are 14 days, 28 days, 56 days, and 63 days. Samples are removed from each chamber and tested for their strong air permeability coefficient.

[0058] As a control group of Example 3, Comparative Example 3 completed the following test:

[0059] Weigh 219.14 g of water glass, add it to 142.87 g of water, heat it to 60°C, stir it evenly, cool it to room temperature, add 15.26 g of NaOH to the above solution, stir it for 30 minutes, and obtain a uniform micellar solution with a water glass modulus of 2.0. Let it stand for 24 hours before use.

[0060] Weigh 1000g of fly ash at a water-binder ratio of 0.3 and pour it into the mixing pot of a cement mortar mixer. Add the micellar solution and stir slowly for 2 minutes, then rapidly for 2 minutes. Place the mixture into a triple mold. Secure the triple mold to a vibrating table and compact the material. Cover with plastic wrap and place in a constant temperature and humidity curing chamber for curing at 90% humidity and 30°C. Curing times are 14, 28, 56, and 63 days. Samples are then taken from each chamber and tested for their air permeability coefficient.

[0061] The experimental results of the air permeability coefficient of Example 3 and Comparative Example 3 are shown in Table 3 as follows:

[0062] Table 3 Air permeability test results of Example 3 and Comparative Example 3

[0063]

[0064] Example 4:

[0065] Weigh 273.72 g of water glass, add it to 178.46 g of water, heat it to 60°C, stir it evenly, cool it to room temperature, add 9.38 g of NaOH to the above solution, stir it for 30 minutes, and obtain a uniform micellar solution with a water glass modulus of 2.5. Let it stand for 24 hours before use.

[0066] Weigh 975g of fly ash, using a water-cement ratio of 0.3, and pour it into the mixing pot of a cement mortar mixer. Then, weigh 25g of nano-barium titanate and pour it into the mixing pot of the cement mortar mixer. Use a cement scraper to preliminarily mix the two powders. Add the micellar solution and stir slowly for 2 minutes, then rapidly for 2 minutes. Then, place the mixture into a triple mold. Secure the triple mold to a vibrating table and compact the material. Cover with plastic wrap and place in a constant temperature and humidity curing chamber for curing at 90% humidity and 30°C. Curing times are 14 days, 28 days, 56 days, and 63 days. Samples are removed from each chamber and tested for their strong air permeability coefficient.

[0067] As a control group of Example 4, Comparative Example 4 completed the following test:

[0068] Weigh 273.72 g of water glass, add it to 178.46 g of water, heat it to 60°C, stir it evenly, cool it to room temperature, add 9.38 g of NaOH to the above solution, stir it for 30 minutes, and obtain a uniform micellar solution with a water glass modulus of 2.5. Let it stand for 24 hours before use.

[0069] Weigh 1000g of fly ash at a water-binder ratio of 0.3 and pour it into the mixing pot of a cement mortar mixer. Add the micellar solution and stir slowly for 2 minutes, then rapidly for 2 minutes. Place the mixture into a triple mold. Secure the triple mold to a vibrating table and compact the material. Cover with plastic wrap and place in a constant temperature and humidity curing chamber for curing at 90% humidity and 30°C. Curing times are 14, 28, 56, and 63 days. Samples are then taken from each chamber and tested for their air permeability coefficient.

[0070] The experimental results of the air permeability coefficient of Example 4 and Comparative Example 4 are shown in Table 4 as follows:

[0071] Table 4 Air permeability test results of Example 4 and Comparative Example 4

[0072]

[0073] Example 5:

[0074] Weigh 109.53 g of water glass, add it to 228.58 g of water, heat it to 60°C, stir it evenly, cool it to room temperature, add 65.69 g of NaOH to the above solution, stir it for 30 minutes, and obtain a uniform micellar solution with a water glass modulus of 0.5. Let it stand for 24 hours before use.

[0075] Weigh 990g of fly ash, using a water-cement ratio of 0.3, and pour it into the mixing pot of a cement mortar mixer. Then, weigh 10g of nano-boron nitride and pour it into the mixing pot of the cement mortar mixer. Use a cement scraper to preliminarily mix the two powders. Add the micellar solution and stir slowly for 2 minutes, then rapidly for 2 minutes. Then, place the mixture into a triple mold. Secure the triple mold to a vibrating table and compact the material. Cover with plastic wrap and place in a constant temperature and humidity curing chamber for curing at 90% humidity and 30°C. Curing times are 14 days, 28 days, 56 days, and 63 days. Samples are removed from each chamber and tested for their strong air permeability coefficient.

[0076] As a control group of Example 5, Comparative Example 5 completed the following test:

[0077] Weigh 109.53 g of water glass, add it to 228.58 g of water, heat it to 60°C, stir it evenly, cool it to room temperature, add 65.69 g of NaOH to the above solution, stir it for 30 minutes, and obtain a uniform micellar solution with a water glass modulus of 0.5. Let it stand for 24 hours before use.

[0078] Weigh 1000g of fly ash at a water-binder ratio of 0.3 and pour it into the mixing pot of a cement mortar mixer. Add the micellar solution and stir slowly for 2 minutes, then rapidly for 2 minutes. Place the mixture into a triple mold. Secure the triple mold to a vibrating table and compact the material. Cover with plastic wrap and place in a constant temperature and humidity curing chamber for curing at 90% humidity and 30°C. Curing times are 14, 28, 56, and 63 days. Samples are then taken from each chamber and tested for their air permeability coefficient.

[0079] The experimental results of the air permeability coefficient of Example 5 and Comparative Example 5 are shown in Table 5 as follows:

[0080] Table 5 Air permeability test results of Example 5 and Comparative Example 5

[0081]

[0082] Example 6:

[0083] Weigh 350.49 g of water glass, add it to 71.48 g of water, heat it to 60°C, stir it evenly, cool it to room temperature, add 39.88 g of NaOH to the above solution, stir it for 30 minutes, and obtain a uniform micellar solution with a water glass modulus of 1.6. Leave it for 24 hours before use.

[0084] Weigh 950g of fly ash, using a water-cement ratio of 0.3, and pour it into the mixing pot of a cement mortar mixer. Then, weigh 50g of nano-silica powder and pour it into the mixing pot of the cement mortar mixer. Use a cement scraper to preliminarily mix the two powders. Add the micellar solution and stir slowly for 2 minutes, then rapidly for 2 minutes. Then, place the mixture into a triple mold. Secure the triple mold to a vibrating table and compact the material. Cover with plastic wrap and place in a constant temperature and humidity curing chamber for curing at 90% humidity and 30°C. Curing times are 14 days, 28 days, 56 days, and 63 days. Samples are removed from each chamber and tested for their strong air permeability coefficient.

[0085] As a control group for Example 6, Comparative Example 6 completed the following test:

[0086] Weigh 350.49 g of water glass, add it to 71.48 g of water, heat it to 60°C, stir it evenly, cool it to room temperature, add 39.88 g of NaOH to the above solution, stir it for 30 minutes, and obtain a uniform micellar solution with a water glass modulus of 1.6. Leave it for 24 hours before use.

[0087] Weigh 1000g of fly ash at a water-binder ratio of 0.3 and pour it into the mixing pot of a cement mortar mixer. Add the micellar solution and stir slowly for 2 minutes, then rapidly for 2 minutes. Place the mixture into a triple mold. Secure the triple mold to a vibrating table and compact the material. Cover with plastic wrap and place in a constant temperature and humidity curing chamber for curing at 90% humidity and 30°C. Curing times are 14, 28, 56, and 63 days. Samples are then taken from each chamber and tested for their air permeability coefficient.

[0088] The experimental results of the air permeability coefficient of Example 6 and Comparative Example 6 are shown in Table 6 as follows:

[0089] Table 6 Test results of air permeability coefficient of Example 6 and Comparative Example 6

[0090]

[0091] Example 7:

[0092] Weigh 350.49 g of water glass, add it to 71.48 g of water, heat it to 60°C, stir it evenly, cool it to room temperature, add 39.88 g of NaOH to the above solution, stir it for 30 minutes, and obtain a uniform micellar solution with a water glass modulus of 1.6. Leave it for 24 hours before use.

[0093] Weigh 950g of fly ash, using a water-cement ratio of 0.3, and pour it into the mixing pot of a cement mortar mixer. Then, weigh 50g of nano-nickel-copper alloy powder and pour it into the mixing pot of the cement mortar mixer. Use a cement scraper to preliminarily mix the two powders. Add the micellar solution and stir slowly for 2 minutes, then rapidly for 2 minutes. Then, place the mixture into a triple mold. Secure the triple mold to a vibrating table and compact the material. Cover with plastic wrap and place in a constant temperature and humidity curing chamber for curing at 90% humidity and 30°C. Curing times are 14 days, 28 days, 56 days, and 63 days. Samples are removed from each chamber and tested for their strong air permeability coefficient.

[0094] As a control group of Example 7, Comparative Example 7 completed the following test:

[0095] Weigh 350.49 g of water glass, add it to 71.48 g of water, heat it to 60°C, stir it evenly, cool it to room temperature, add 39.88 g of NaOH to the above solution, stir it for 30 minutes, and obtain a uniform micellar solution with a water glass modulus of 1.6. Leave it for 24 hours before use.

[0096] Weigh 1000g of fly ash at a water-binder ratio of 0.3 and pour it into the mixing pot of a cement mortar mixer. Add the micellar solution and stir slowly for 2 minutes, then rapidly for 2 minutes. Place the mixture into a triple mold. Secure the triple mold to a vibrating table and compact the material. Cover with plastic wrap and place in a constant temperature and humidity curing chamber for curing at 90% humidity and 30°C. Curing times are 14, 28, 56, and 63 days. Samples are then taken from each chamber and tested for their air permeability coefficient.

[0097] The experimental results of the air permeability coefficient of Example 7 and Comparative Example 7 are shown in Table 7 as follows:

[0098] Table 7 Test results of air permeability coefficient of Example 7 and Comparative Example 7

[0099]

[0100] Example 8:

[0101] Weigh 350.49 g of water glass, add it to 71.48 g of water, heat it to 60°C, stir it evenly, cool it to room temperature, add 39.88 g of NaOH to the above solution, stir it for 30 minutes, and obtain a uniform micellar solution with a water glass modulus of 1.6. Leave it for 24 hours before use.

[0102] Weigh 990g of fly ash, using a water-cement ratio of 0.3, and pour it into the mixing pot of a cement mortar mixer. Then, weigh 10g of nano-iron powder and pour it into the mixing pot of the cement mortar mixer. Use a cement scraper to preliminarily mix the two powders. Add the micellar solution and stir slowly for 2 minutes, then rapidly for 2 minutes. Then, place the mixture into a triple mold. Secure the triple mold to a vibrating table and compact the material. Cover with plastic wrap and place in a constant temperature and humidity curing chamber for curing at 90% humidity and 30°C. Curing times are 14 days, 28 days, 56 days, and 63 days. Samples are removed from each chamber and tested for their strong air permeability coefficient.

[0103] As a control group of Example 8, Comparative Example 8 completed the following test:

[0104] Weigh 350.49 g of water glass, add it to 71.48 g of water, heat it to 60°C, stir it evenly, cool it to room temperature, add 39.88 g of NaOH to the above solution, stir it for 30 minutes, and obtain a uniform micellar solution with a water glass modulus of 1.6. Leave it for 24 hours before use.

[0105] Weigh 1000g of fly ash at a water-binder ratio of 0.3 and pour it into the mixing pot of a cement mortar mixer. Add the micellar solution and stir slowly for 2 minutes, then rapidly for 2 minutes. Place the mixture into a triple mold. Secure the triple mold to a vibrating table and compact the material. Cover with plastic wrap and place in a constant temperature and humidity curing chamber for curing at 90% humidity and 30°C. Curing times are 14, 28, 56, and 63 days. Samples are then taken from each chamber and tested for their air permeability coefficient.

[0106] The experimental results of the air permeability coefficient of Example 8 and Comparative Example 8 are shown in Table 8 as follows:

[0107] Table 8 Air permeability test results of Example 8 and Comparative Example 8

[0108]

[0109] Example 9:

[0110] Weigh 350.49 g of water glass, add it to 71.48 g of water, heat it to 60°C, stir it evenly, cool it to room temperature, add 39.88 g of NaOH to the above solution, stir it for 30 minutes, and obtain a uniform micellar solution with a water glass modulus of 1.6. Leave it for 24 hours before use.

[0111] Weigh 990g of fly ash, using a water-cement ratio of 0.3, and pour it into the mixing pot of a cement mortar mixer. Then, weigh 10g of nano-carbon powder and pour it into the mixing pot of the cement mortar mixer. Use a cement scraper to preliminarily mix the two powders. Add the micellar solution and stir slowly for 2 minutes, then rapidly for 2 minutes. Then, place the mixture into a triple mold. Secure the triple mold to a vibrating table and compact the material. Cover with plastic wrap and place in a constant temperature and humidity curing chamber for curing at 90% humidity and 30°C. Curing times are 14 days, 28 days, 56 days, and 63 days. Samples are removed from each chamber and tested for their strong air permeability coefficient.

[0112] As a control group for Example 9, Comparative Example 9 completed the following test:

[0113] Weigh 350.49 g of water glass, add it to 71.48 g of water, heat it to 60°C, stir it evenly, cool it to room temperature, add 39.88 g of NaOH to the above solution, stir it for 30 minutes, and obtain a uniform micellar solution with a water glass modulus of 1.6. Leave it for 24 hours before use.

[0114] Weigh 1000g of fly ash at a water-binder ratio of 0.3 and pour it into the mixing pot of a cement mortar mixer. Add the micellar solution and stir slowly for 2 minutes, then rapidly for 2 minutes. Place the mixture into a triple mold. Secure the triple mold to a vibrating table and compact the material. Cover with plastic wrap and place in a constant temperature and humidity curing chamber for curing at 90% humidity and 30°C. Curing times are 14, 28, 56, and 63 days. Samples are then taken from each chamber and tested for their air permeability coefficient.

[0115] The experimental results of the air permeability coefficient of Example 9 and Comparative Example 9 are shown in Table 9 as follows:

[0116] Table 9 Air permeability test results of Example 9 and Comparative Example 9

[0117]

[0118] With reference to Examples 1 to 9 and Comparative Examples 1 to 9, the air permeability test of the prepared geopolymer solidified material in the embodiments of the present invention revealed that the addition of the nanopowder additive significantly improved the air permeability of the geopolymer solidified material, thereby significantly improving the air tightness of the geopolymer. In particular, when the alkali content in the activator accounted for 13% to 16% of the total ash content of the fly ash and the nanopowder additive, and the nanopowder additive accounted for 10% to 20% of the total ash content of the fly ash and the nanopowder additive, the synergistic effect between the various components in the geopolymer was further enhanced, and the air tightness was improved without affecting the mechanical strength and stability.

[0119] Based on the same inventive concept, an embodiment of the present invention further provides a high-air-tightness geopolymer solidified material prepared by the above-mentioned method for preparing a high-air-tightness geopolymer solidified material.

[0120] Based on the same inventive concept, an embodiment of the present invention further provides a method for preparing a highly airtight geopolymer solidified material, and its application in a construction project. The highly airtight geopolymer solidified material in this embodiment can be used as a building material in a construction project.

[0121] Based on the same inventive concept, an embodiment of the present invention further provides an application of the aforementioned high-gas-tightness geopolymer solidified material in well completion or cementing. Due to its significant gas-tightness, the high-gas-tightness geopolymer solidified material in this embodiment can be used as a cement replacement in well completion or cementing.

[0122] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if such changes and modifications fall within the scope of the claims and their equivalents, the present invention is intended to include such changes and modifications.

Claims

1. A method for preparing a highly airtight geopolymer solidified material, characterized in that: include: Add an activator consisting of water glass and sodium hydroxide into water, heat and stir to obtain a micellar solution, and then cool to room temperature for use; According to the water-binder ratio of the total amount of water in the water glass and the added water to the total amount of fly ash and the nano powder additive being 0.3, the fly ash and the nano powder additive are weighed, and the fly ash and the nano powder additive are poured into the mixing pot of the cement mortar mixer for preliminary mixing; wherein the alkali content in the activator accounts for 9% to 16% of the total amount of fly ash and the nano powder additive; and the nano powder additive accounts for 1% to 20% of the total amount of fly ash and the nano powder additive; The micelle solution is poured into the stirring pot, and stirred and mixed with the preliminarily mixed fly ash and the nano powder additive to prepare the geopolymer solidified material.

2. The preparation method according to claim 1, characterized in that: The alkali content in the activator accounts for 10% to 16% of the total ash content of the fly ash and the nano powder additive; the nano powder additive accounts for 1% to 3% of the total ash content of the fly ash and the nano powder additive, or the nano powder additive accounts for 10% to 20% of the total ash content of the fly ash and the nano powder additive.

3. The method according to claim 2, characterized in that The alkali content in the activator accounts for 13% to 16% of the total ash content of the fly ash and the nanometer powder additive; the nanometer powder additive accounts for 10% to 20% of the total ash content of the fly ash and the nanometer powder additive.

4. The method according to any one of claims 1 to 3, characterized in that The modulus of the water glass is 0.5 to 2.

5.

5. The method according to any one of claims 1 to 3, characterized in that: The nano powder additive is at least one of the following nano powders: nano oxide, nano non-metal and nano metal.

6. The method according to any one of claims 1 to 3, characterized in that: In the above steps, the micelle solution is obtained by heating and stirring uniformly, the heating parameter is heating to 60° C., and the stirring parameter is stirring for 30 minutes.

7. The method according to any one of claims 1 to 3, characterized in that: In the above steps, the stirring parameters for mixing the micellar solution with the coal powder and the nano-powder additive are: first stirring slowly for 2 minutes and then stirring quickly for 2 minutes.

8. A highly airtight geopolymer cured product prepared by the method for preparing a highly airtight geopolymer cured product according to any one of claims 1 to 7.

9. Use of a highly airtight geopolymer solidified material prepared by the method for preparing a highly airtight geopolymer solidified material according to any one of claims 1 to 7 in construction engineering.

10. Use of a high-gas-tightness geopolymer solidified material prepared by the method for preparing a high-gas-tightness geopolymer solidified material according to any one of claims 1 to 7 in well completion or cementing.

Citation Information

Patent Citations

  • Rapidly-hardened high-strength fly ash geopolymer material and preparation method thereof

    CN113416025A